(untitled) (Journal of Scientific Research, 2012)
The treatment of tannery effluent was carried out based on the locally available commercial grade lime. Collected tannery effluent was acidic (pH 3.94) in nature with total chromium content, chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solids (TDS) and the conductivity at 30°C were 987 mg/L, 3175.32 mg O2/L, 22915 mg/L, 13360 mg/L and 60.7 mS/cm, respectively. The effluent was treated by chemical precipitation method and the dependency on pH in the treatment was investigated by altering the pH from 6.0 to 11.0 by the gradual addition of lime slurry. The treated effluents were characterized primarily in terms of COD and conductivity and we obtained lowest COD (345 mg O2/L) and conductivity (21.4 mS/cm at 30°C) values at pH 9. Then a large scale treatment was carried out with 20.0 L of the effluent in the same experimental condition at pH 9 and the removal of chromium, COD, TSS, TDS and conductivity (at 30°C) were achieved up to 99.79, 60.99, 97.22, 98.27 and 41.85%, respectively. Chloride concentration was also measured before and after treatment but no significant change was observed. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.12557 J. Sci. Res. 5 (1), 143-150 (2013)